KUALITAS JASA SISTEM INFORMASI DAN KEPUASAN PARA PENGGUNANYA - RUSMA MULYADI (Jurnal Bisnis dan Akuntansi, 1999)
A crucial concern of both management information systems researchers and practitioners is improving user satisfaction with an organization's IS department. This study was undertaken in order to futher examine the relationship betwen user information satisfaction and service quality of organization's IS department, the facators contributed to better prediction of user information satisfaction and the variations of user's zone of tolerance for different service attributes/dimensions. To overcome the external validity problem, this study was held in real business environment setting and the respondents are users of IS departments from many different companies in Indonesia. There were several findings of this study. Firs, this study supported a significant positive relationship between user information satisfaction and service quality. Second, there were three significant predicors of user information satisfactions, the first two predictors are the original factors of the traditional user information satisfaction instrument (i.e., quality of information product and attitude towars IS department staff and services) and the third one is the aspect of service quality i.e. 'reliability'. Third, concerning the variation of users' zone of tolerance for different aspects of service quality, this study still can not reject the null hypothesis that there are no variation of users' zone of tolerance for different aspects of service quality. Implications for research and practice resulting from these findings are discussed.